Profile of tuberculous pneumothorax and comparison with pulmonary tuberculosis without pneumothorax - Yellapu, Gayatri D.; Vipparthi, Surya K.; Vangara, Rohini K. (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis is the most common cause of secondary spontaneous pneumothorax (SSP) in India. The prevalence of SSP in patients with pulmonary tuberculosis (PTB) is between 1- 3%. There were only few studies in the literature that specifically analyze tuberculous PNTX. In a study from this hospital, author found PTB was the most common cause of SSP. Now, author aimed at studying the clinical profile of tuberculosis associated PNTX cases and compared with pulmonary tuberculosis cases without PNTX. Methods: This was a single centre prospective observational case control study done at a tertiary care hospital. Fifty patients of tuberculous pneumothorax as cases, and 100 patients of pulmonary tuberculosis without pneumothorax were taken as control. The demographic data, clinical presentation, and radiologic presentation, outcomes after treatment were recorded in both the groups. The data was analyzed using statistical software (SPSS) using appropriate statistical tools. Results: The mean age of patients in the PNTX group was 38.18±14.132, where as in the control group it was 45.29±14.89 (p-value of 0.0052). Past history of tuberculosis was present in 27 (54%) cases of PNTX group and in 41 (41%) cases in the control group (p-value of 0.091). The mean duration of length of hospital stay in PNTX group was 16.5±11.865 days and in non-pneumothorax group was 6.2±2.54 days (p-value was 0.0001). Conclusions: Tuberculous pneumothorax was more common between 30-40 yrs age group. Gender and smoking have no association with PNTX. Tuberculous pneumothorax was more common in previously treated cases of TB. Patients with tuberculous PNTX have prolonged hospital stay and complications resulting in increased morbidity, financial burden and mortality.